Multicenter Observational Study of the First-Generation Intravenous Blood Glucose Monitoring System in Hospitalized Patients. (30th June 2015) - Bochicchio, Grant V.; Hipszer, Brian R.; Magee, Michelle F.; Bergenstal, Richard M.; Furnary, Anthony P.; Gulino, Angela M.; Higgins, Michael J.; Simpson, Peter C.; Joseph, Jeffrey I.
Background: Current methods of blood glucose (BG) monitoring and insulin delivery are labor intensive and commonly fail to achieve the desired level of BG control. There is great clinical need in the hospital for a user-friendly bedside device that can automatically monitor the concentration of BG safely, accurately, frequently, and reliably. Methods: A 100-patient observation study was conducted at 6 US hospitals to evaluate the first generation of the Intravenous Blood Glucose (IVBG) System (Edwards Lifesciences LLC & Dexcom Inc). Device safety, accuracy, and reliability were assessed. A research nurse sampled blood from a vascular catheter every 4 hours for ≤ 72 hours and BG concentration was measured using the YSI 2300 STAT Plus Analyzer (YSI Life Sciences). The IVBG measurements were compared to YSI measurements to calculate point accuracy. Results: The IVBG systems logged more than 5500 hours of operation in 100 critical care patients without causing infection or inflammation of a vein. A total of 44135 IVBG measurements were performed in 100 patients with 30231 measurements from the subset of 75 patients used for accuracy analysis. In all, 996 IVBG measurements were time-matched with reference YSI measurements. These pairs had a mean absolute difference (MAD) of 11.61 mg/dl, a mean absolute relative difference (MARD) of 8.23%, 93% met 15/20% accuracy defined by International Organization for Standardization 15197:2003 standard, and 93.2% were in zone A of the Clarke error grid. The IVBG sensors were exposed to more than 200 different medications with no observable effect on accuracy. Conclusions: The IVBG system is an automated and user-friendly glucose monitoring system that provides accurate and frequent BG measurements with great potential to improve the safety and efficacy of insulin therapy and BG control in the hospital, potentially leading to improved clinical outcomes.